Trustworthiness verification method for social media information - Khairuddin Yap, Mohamad Nazri (2022)
The pervasive use of social media has generated massive information sharing among its users. Given the fluidity and excessive information available online, issues relating to the trustworthiness of information have become a concern among the users and authorities. Sensational and unreliable information shared in the social media may cause and harm the reputation of an individual, product, organization, or government. There exist several ways on how the society could overcome this issue of information trustworthiness by referring to the website of the related agencies pertaining the issues, manually search for information, or even depending on the information to be viral and shared through the social media. However, these methods did not come handy and time consuming allowing the society to get incomplete trustworthiness of information. Dealing with trustworthiness of information requires the society to consider and examine several aspects about the information itself such as the locality of the information, the reputation, the trusted source and the time or period of the information. Therefore, the objectives for this study are three folds. First is to define the factors of the trustworthiness of information for social media. At this stage, it is important to identify the determinants for information trustworthiness through scholarly review as well as from the surveys from the social media users. Second, is to propose a verification method that verifies the degree of perceived trustworthiness of information in social media. The determining factors are important to develop rules for verifying the information trustworthiness. These rules will provide the degree of the trustworthiness level for the determining factors which had been identified. The third objective is to evaluate the usability of the approach that verifies the degree of perceived trustworthiness of information in the social media. The usability of the rules is evaluated by conducting usability test from the random social media users. Furthermore, we have employed a process-based research method that starts with analyzing the most influencing factors of trustworthiness through literature and comprehensive survey to confirm the factors. Then, we have constructed the rules to calculate the trustworthiness percentage and realized the approach with a tool called TrustCrawler. Nevertheless, with the determining factors which form the rules for the verification will contribute for the level of the information trustworthiness. The verification percentage will determine the level of trustworthiness to indicate the significance of the information. It is believed that the adoption of verification approach will help to educate and make the public users aware of the level of trustworthiness of information, hence developing an informed, safe, and ethical users of media content. This study underlines how critical it is for social media users to comprehend and be properly informed about the information they acquire. In future, this research could extend the information trustworthiness verification method to other social media platforms.